2018
DOI: 10.1016/j.scico.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Agile validation of model transformations using compound F-Alloy specifications

Abstract: Model transformations play a key role in model driven software engineering approaches. Validation of model transformations is crucial for the quality assurance of software systems to be constructed. The relational logic based specification language Alloy and its accompanying tool the Alloy Analyzer have been used in the past to validate properties of model transformations. However Alloy based analysis of transformations suffers from several limitations. On one hand, it is time consuming and does not scale well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…As the result, we achieve an integrated life-cycle of DSMM encompassing five phases, where V&V techniques are first class citizens. Please note that while doing that we also benefit from our earlier experiences, reported among others in [27,49,80], as well as experiences reported in the literature. Last but not least, building on the results of our analysis as well as on our subjective assessment of the state of the field of enterprise modeling, we formulate five desiderata, from the perspectives of practice, research and education, respectively, together with some initial ideas as to how they can be achieved.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…As the result, we achieve an integrated life-cycle of DSMM encompassing five phases, where V&V techniques are first class citizens. Please note that while doing that we also benefit from our earlier experiences, reported among others in [27,49,80], as well as experiences reported in the literature. Last but not least, building on the results of our analysis as well as on our subjective assessment of the state of the field of enterprise modeling, we formulate five desiderata, from the perspectives of practice, research and education, respectively, together with some initial ideas as to how they can be achieved.…”
mentioning
confidence: 57%
“…On the semantic side, these example models basically constitute the extensional definition of the language. Omissions (e.g., missing well-formedness rules), excess (e.g., unnecessary concepts), or mismatching (e.g., a relation between wrong types of concepts) can be detected by simply reviewing these example models [48,49,112]. The reviewing activity is further enhanced when the example models are visualized in a domain-specific notation, because it makes possible for domain experts and non-technical users to understand the example models, hence, be able to pinpoint errors.…”
Section: Formalize Phasementioning
confidence: 99%
See 1 more Smart Citation
“…As described in the proposed conceptual model, and inline with the widely adopted notion of testing [198], we focus on testing approaches running the MT under test to identify failures, often referred to as łdynamic testingž [211]. Formal and static (i.e., those not running the MT under test) approaches for identifying bugs in MTs such as formal veriication [194,199,231,245,255,256] and model checking [262] have been largely studied in related papers and surveys [164,182,235] and are out of the scope of our work. We also excluded papers on model-based testing [208,213,218], where MTs are often used as a means to test other programs.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…To support that the soundness results in Table 1 are significant, we rely on the small scope hypothesis, which basically claims most design errors can be found in small counterexamples [20]. Experimental results suggest that exhaustive testing within a small finite domain does indeed catch all type system errors in practice [21], and many case studies using the formal language and tool Alloy have confirmed the hypothesis by performing an analysis in a variety of scopes and showing, retrospectively, that a small scope would have sufficed to find all the bugs discovered [22].…”
Section: Verifying Soundnessmentioning
confidence: 99%